Umbilical catheter placement aided by coronary guidewires - Katarzyna Gendera; Stanimir Georgiev; Peter Ewert; Stefan Eckstein; Christoph Fusch; Niels Rochow (Molecular and Cellular Pediatrics, 2023)
Abstract Catheterization of the umbilical vessels has proven to be an effective and relatively rapid method for gaining central vascular access in neonates. However, it can be technically difficult, the procedure may last 30 min or longer, and it can be associated with complications in some patients. We suggest using a coronary guidewire during catheterization of umbilical vessels to support the placement of umbilical catheters and significantly reduce a risk for complications. We tested the proposed technique in 6 successful ex vivo bench tests of catheterization of the umbilical vessels in stillborn piglets immediately after birth. We are confident that using coronary guidewire as a guiding tool during catheterization of the umbilical vessels is a rapid and safe method. We expect that it allows to obtain a vascular access with lower risk for dangerous procedural complications, which could be a lifesaving in critically ill patients. However, the approach needs to be validated in a comparative study in neonates.